Control De Gestion En La Empresa Altec S.A - Alava Aguirre, Ronny Allan (2018)
In a market as demanding as the current one, companies seek to make improvements to be more competitive. Management controls are an important factor in the economy of companies to achieve this goal and thus be more efficient. Therefore, it is necessary to maintain an efficient financial management, due that in the absence of adequate controls in a company, this causes an increase in costs, deficiencies in their processes and loss of customers causing low income sales, expenses generated by breach of contracts, in addition to dissatisfaction of the client causes a negative image of the company. The present case is focused on the management control of the company Altec S.A located in the Babahoyo county of Los Ríos province, is dedicated to the sale of materials raw materials such as aluminum and glass and the manufacture of showcases, hangers and windows and doors. What is pursued with the realization of the case is to know the weaknesses in the financial management of the company, which causes them to incur a number of deficiencies that could be prevented or corrected in time and thus reduce risks and improve profitability of the industry. The research subline to which the case study is related is the Management of accounting information. The methodology used in this project is of type Exploratory, because during the internship process I was able to know the deficiencies in the management of costs that originate in this company, it is also a field investigation 3 because the whole process is carried out directly in the company, the techniques used in the study is the observation and the interview, these allow me to know the real situation of the problem, identifying the needs of the area. Thus, through this case it has been proposed to have a better vision of the institutional reality of the company, so that the administrators look for the increase of profitability by improving services, modifying strategies, creating policies and regulating the performance of its operators, project the growth of funds available so that it has a balance with the credits that will be offered to customers.